AR/VR Tutorial System for Human-Robot Teaming - Jones, Colin; Novitzky, Michael; Korpela, Christopher (2021 IEEE 11th Annual Computing and Communication Workshop and Conference (CCWC), 2021)
The role of human-robot teaming (HRT), or the interaction between humans and robots to complete tasks, is becoming increasingly important in the modern age. From medicine to military applications, robots have established themselves as powerful tools in the completion of human-directed objectives. Given the importance of this teaming, it is equally important that there exists a system to develop such partnerships. For this purpose we present a tutorial based on the framework of the Project Aquaticus human-robot teaming test-bed, where participants in previous experiments felt overwhelmed while working with an autonomous robot teammate. To improve and develop this participant-robot relationship, we developed a tutorial for HRT using the Unity game engine. The Project Aquaticus test-bed centers around a game of capture-the-flag played in boats on the water, where each team is equipped with two human-steered boats and two autonomous robot teammates. The tutorial is designed based on the analysis of previous literature and includes features found in other, effective training systems and tutorials. The creation of this automated tutorial system shows promise in improving the effectiveness of HRT in the context of Project Aquaticus. In the near future, the effectiveness of this tutorial system will be tested with human subjects to evaluate improvements to situational awareness and cognitive load.